Development of Student Worksheets (LKPD) Based on the Scientific Approach in Mathematics Learning for Grade VIII at MTsN 3 Agam in the 2023/2024 Academic Year - Sri Devi Hasani, Sri Devi Hasani; Isnaniah; Arifmiboy; M.Imamuddin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the problems identified in Grade VIII of MTsN 3 Agam, namely the lack of teaching materials and the use of student worksheets (LKPD) that are not yet based on the scientific approach. The existing LKPDs at the school are publisher-produced and do not align with the characteristics of the students, making it difficult for them to understand the mathematics material being taught. This study is a development research or Research and Development (R&D) using the ADDIE development model. The research steps carried out include the analysis, design, development, implementation, and evaluation stages. Based on the development research conducted, the resulting LKPD has a validity level categorized as very valid at 82.727%, a practicality level categorized as very practical at 83.74%, and an effectiveness level categorized as very effective at 80.64%. Therefore, it can be concluded that the LKPD based on the Scientific Approach in Mathematics Learning for Grade VIII of MTsN 3 Agam that was developed is valid, practical, and effective.